(untitled) (Journal of Scientific Research, 2012)
Jute-mat (JM) reinforced polyvinylchloride (PVC) composites were prepared with various contents of acetylated and non-acetylated JM by heat-pressed method at 160 °C to obtain a neat PVC (NPVC), untreated PVC-JM composites (UC) and treated PVC-JM composites (TC). Structural, mechanical, surface morphological and thermal properties of a NPVC and a series of UC and TC were characterized by Fourier transform infrared (FTIR) spectrometry, mechanical test and differential thermal analyses (DTA). Water intake (WI) measurements of these samples were also performed. FTIR spectra show distinct absorption peaks for NPVC and UC and TC, suggesting a modified surface texture of JM fiber. While the NPVC does not show any water absorption, the UC exhibit higher WI than TC, indicating that the hydrophilic moiety of JM is filled up by the acetyl group. Tensile strength, flexural strength, Youngs modulus and tangent modulus of TC are observed to be higher than those of NPVC and UC. Surface micrographs reveal a better adhesion between acetylated JM and PVC than between non-acetylated JM and PVC. The decomposing temperature of TC is observed to be higher than that of NPVC and UC. Enhancement of various properties of acetylated JM-PVC composites is elaborately discussed in this paper. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i1.11798 J. Sci. Res. 5 (1), 13-23 (2013)